An ultrathin in situ silicification layer developed by an electrostatic attraction force strategy for ultrahigh-performance oil–water emulsion separation. Issue 42 (15th October 2019) - Zhang, Lei; Lin, Yuqing; Wu, Haochen; Cheng, Liang; Sun, Yuchen; Yasui, Tomoki; Yang, Zhe; Wang, Shengyao; Yoshioka, Tomohisa; Matsuyama, Hideto
Abstract : Development of SiO2 -d-PK membrane via electrostatic attraction forced strategy for oil–water emulsions separation. Abstract : Membrane fouling caused by oil or other pollutants is one of the major challenges for membrane separation technology used for emulsified oil/water purification. Aiming at the realization of comprehensive fouling-resistant/fouling-release properties, and the further achievement of long-term cyclic separation, an ultrathin silica (SiO2 ) layer is conformally engineered onto a porous polyketone (PK) substrate via the electrostatic attraction force silicification process. This in situ silicification forms an ultrathin and superhydrophilic/underwater superoleophobic interface structure that allows the realization of ultrahigh water permeance up to 7533 L m −1 h −1 bar −1, an exceptionally high emulsion flux up to 6000 L m −1 h −1 bar −1 (close to pure water permeance), and a high rejection of >99.9% against various oily emulsions. The unique design of the superhydrophilic silicification layer grown on the hydrophilic PK substrate also endowed the membrane with comprehensive antifouling properties against a broad range of oily emulsions containing various pollutants such as proteins, surfactants, and other natural organic materials (NOM), from which a nearly 100% recovery ratio of permeation flux could be obtained after several cycles of oily emulsion filtration. The use of an inorganic SiO2 modified layer incorporated into a highly chemically inert PK substrate (SiO2 -d-PK membrane) also enabled the application of the SiO2 -d-PK membrane under more challenging conditions, where its great tolerance and long-term stability toward salty and strongly acidic/alkaline solutions and various organic solvents were further demonstrated. Overall, this study provides an insight into engineering an ultrathin membrane with ultralow fouling-propensity for treating challenging oily emulsions.